Definition of liquidation property value - Gnenny, Oleg; Dailydka, Stasys; Lingaitis, Vytautas (Business, Management and Economics Engineering, 2013)
The article examines the interrelation of market and liquidation value of the appraisal subject. It was established that the approach of “break-even” sale of a subject at liquidation value, which is predominating in the literature sources, shows the results essentially different from the ratio of the prices of free and accelerated sales that can be observed on the market. The article offers an alternative approach to definition of market value coefficient, which considers switching to liquidation value. This approach is based on functional dependence of the coefficient on the ratio of limited and unlimited period of exposition.